2006
DOI: 10.1186/ar2021
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor: a mediator of matrix metalloproteinase-2 production in rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by destruction of bone and cartilage, which is mediated, in part, by synovial fibroblasts. Matrix metalloproteinases (MMPs) are a large family of proteolytic enzymes responsible for matrix degradation. Macrophage migration inhibitory factor (MIF) is a cytokine that induces the production of a large number of proinflammatory molecules and has an important role in the pathogenesis of RA by promoting inflammation and angiogenesis.In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 66 publications
(64 reference statements)
1
30
0
1
Order By: Relevance
“…MMP-2 induction by MIF in arthritic synovial fibroblasts was inhibitable, among other kinase pathway blockers, by a JNK I small molecule inhibitor [39]. MMP-9 and -13 induction in osteoblasts is also enhanced by activation of MIF and AP1, but MIF-mediated activation of c-Jun and c-Fos in these cells was independent of JNK and rather seemed to be due to an MIF/ERK1/2-dependent induction of c-Fos/c-Jun gene transcription [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP-2 induction by MIF in arthritic synovial fibroblasts was inhibitable, among other kinase pathway blockers, by a JNK I small molecule inhibitor [39]. MMP-9 and -13 induction in osteoblasts is also enhanced by activation of MIF and AP1, but MIF-mediated activation of c-Jun and c-Fos in these cells was independent of JNK and rather seemed to be due to an MIF/ERK1/2-dependent induction of c-Fos/c-Jun gene transcription [58].…”
Section: Discussionmentioning
confidence: 99%
“…The MIF/CD74 axis has not been shown to stimulate the JNK pathway, although MIF release inhibits signalling through JNK in ischemic cardiomyocytes [38]. MIF-induced MMP-2 production in rheumatoid synovial fibroblasts required activation of protein kinase C, JNK, and SRC signalling pathways [39]. On the other hand, Yu et al showed that MIF induces MMP-9 expression in murine macrophages mainly via the ERK1/2 MAPK pathway and only to a minor extent through JNK [40].…”
Section: Introductionmentioning
confidence: 99%
“…MIF is an important cytokine that regulates both adaptive and immune responses 3. It is a potent pro-inflammatory cytokine that has been reported to stimulate TNF and IL-6 expression4 and an important downstream marker of inflammation. C-reactive protein (CRP) is one of the acute phase proteins that increase during systemic inflammation 5,6.…”
Section: Introductionmentioning
confidence: 99%
“…Remodeling of the extracellular matrix by MMPs is important in angiogenesis. Among the various subtypes of MMPs, MMP-1, MMP-2 and MMP-9 expression levels have been demonstrated in rheumatoid synovial macrophages [20,21]. Moreover, synovial macrophages also express tissue inhibitors of MMPs (TIMPs) that contrast the effects of MMPs [20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, macrophage migration-inhibitory factor (MIF) is expressed by macrophages in the synovium, where it is responsible for inducing macrophage production of angiogenic agents, including TNF-α, IL-1, IL-6, IL-8/CXCL8 and MMPs production [21,39]. In animal models of rheumatoid arthritis, MIF antagonism or deficiency result in decreased disease severity [58].…”
Section: Introductionmentioning
confidence: 99%